Ordinary Images. Stanley Abe. - Barrett, T. H. (Buddhist Studies Review, 2004)
Ordinary Images. Stanley Abe. University of Chicago Press, Chicago and London 2002. xxvi, 373 pp. 65.00/£45.50. ISBN 0-226-00044-3.